The Phonology of ‘Idle Glottis’ Consonants in the Mehri of Oman (Modern South Arabian) - Bendjaballah, Sabrina; Ségéral, Philippe 1954- (2014)
The goal of this paper is to elucidate the phonological effects of the class of voiceless non-ejective consonants (henceforth ‘idle glottis’ consonants, noted ©-consonants) in the Mehri of Oman. We review the processes involving this class of consonants, some of which have remained unnoticed up to now, and show that, contrary to what is asserted in the literature, single ©-consonants never trigger any particular effect. The ‘idle glottis’ feature becomes relevant when two ©-consonants are adjacent at the word-edge (initial and final). In this context, the two ©-consonants constitute a pseudogeminate. Word-finally, the formation of a pseudogeminate closes the preceding syllable, which in turn shortens the tonic vowel, leading to apparently deviant paradigms on the surface. Word-initially, we show that the prefixal allomorphies characteristic of the Mehri of Oman are controlled by the formation of pseudogeminate /h-©/, with total assimilation of h-. The resulting initial geminate is affected by a phenomenon of latency: its first branch remains phonetically unrealized.